Microbial Groundwater Quality Status of Hand-Dug Wells and Boreholes in the Dodowa Area of Ghana - George Lutterodt (International Journal of Environmental Research and Public Health, 2018)
To assess the suitability of water sources for drinking purposes, samples were taken from groundwater sources (boreholes and hand-dug wells) used for drinking water in the Dodowa area of Ghana. The samples were analyzed for the presence of fecal indicator bacteria (Escherichia coli) and viruses (Adenovirus and Rotavirus), using membrane filtration with plating and glass wool filtration with quantitative polymerase chain reaction (PCR), respectively. In addition, sanitary inspection of surroundings of the sources was conducted to identify their vulnerability to pollution. The presence of viruses was also assessed in water samples from the Dodowa River. More than 70% of the hand-dug wells were sited within 10 m of nearby sources of contamination. All sources contained E. coli bacteria, and their numbers in samples of water between dug wells and boreholes showed no significant difference (p = 0.48). Quantitative PCR results for Adenovirus indicated 27% and 55% were positive for the boreholes and hand-dug wells, respectively. Samples from all boreholes tested negative for the presence of Rotavirus while 27% of the dug wells were positive for Rotavirus. PCR tests of 20% of groundwater samples were inhibited. Based on these results we concluded that there is systemic microbial and fecal contamination of groundwater in the area. On-site sanitation facilities, e.g., pit latrines and unlined wastewater drains, are likely the most common sources of fecal contamination of groundwater in the area. Water abstracted from groundwater sources needs to be treated before use for consumption purposes. In addition, efforts should be made to delineate protected areas around groundwater abstraction points to minimize contamination from point sources of pollution.